Baseline Determination Options and their Impact on Maritime Boundary Determination – Case Study: the Cyprus Maritime Boundary Opposite the Syrian Coast - بوبو معن (Latakia University Journal -Engineering Sciences Series, 2023)
Each coastal State has a set of rights and powers over the waters adjacent to its coast. These rights and powers have been affirmed in a set of international conventions and treaties, the most of which was in 1982, when the United Nations Convention on the Law of the Sea, (UNCLOS) was adopted. The maritime boundaries are divided into three sections: Territorial Sea (TS) (12 nautical miles), Contiguous Zone (CZ) (24 nautical miles) and the Exclusive Economic Zone (EEZ) (up to 200 nautical miles), all of which are drawn from the same base line. Since, even according to maritime laws, there are different interpretations of the methods of determination this line, and considering that, such interpretations lead to the possession of larger water areas at the expense of the water areas of the opposite or neighboring countries. This study was conducted on the situation of the Cyprus border opposite to the Syrian Arab Republic. Where the different options for base line determination of the eastern and southern coasts of Cyprus, and the impact of those possibilities on the determination of other maritime boundaries were reviewed. The study concluded that whatever the method of drawing the base line, its impact on the final border (contiguous zone) will be limited and will give almost the same result, and will not have a significant impact on the Syrian maritime border. Keywords: Base line, Territorial Sea (TS), Territorial limits, Maritime Boundary, Contiguous Zone (CZ), Exclusive Economic Zone (EEZ), United Nations Convention on the Law of the Sea, UNCLOS, Convention on the Territorial Sea and the Contiguous Zone 1958.